The diversified role of mitochondria in ferroptosis in cancer - Liu, Yu’e; Lu, Shiping; Wu, Lei-lei; Yang, Liang; Yang, Lixue; Wang, Jinghan (Cell death & disease, 2023)
Ferroptosis is a form of regulated cell death induced by iron-dependent lipid peroxidation, and it has been studied extensively since its discovery in 2012. Induced by iron overload and ROS accumulation, ferroptosis is modulated by various cellular metabolic and signaling pathways. The GSH-GPX4 pathway, the FSP1-CoQ10 pathway, the GCH1-BH4 pathway, the DHODH-CoQH2 system and the sex hormones suppress ferroptosis. Mitochondrial iron metabolism regulates ferroptosis and mitochondria also undergo a morphological change during ferroptosis, these changes include increased membrane density and reduced mitochondrial cristae. Moreover, mitochondrial energy metabolism changes during ferroptosis, the increased oxidative phosphorylation and ATP production rates lead to a decrease in the glycolysis rate. In addition, excessive oxidative stress induces irreversible damage to mitochondria, diminishing organelle integrity. ROS production, mitochondrial membrane potential, mitochondrial fusion and fission, and mitophagy also function in ferroptosis. Notably, some ferroptosis inhibitors target mitochondria. Ferroptosis is a major mechanism for cell death associated with the progression of cancer. Metastasis-prone or metastatic cancer cells are more susceptible to ferroptosis. Inducing ferroptosis in tumor cells shows very promising potential for treating drug-resistant cancers. In this review, we present a brief retrospect of the discovery and the characteristics of ferroptosis, then we discuss the regulation of ferroptosis and highlight the unique role played by mitochondria in the ferroptosis of cancer cells. Furthermore, we explain how ferroptosis functions as a double-edged sword as well as novel therapies aimed at selectively manipulating cell death for cancer eradication.